Tolerance and Biological Removal of Fungicides by Trichoderma Species Isolated From the Endosphere of Wild Rubiaceae Plants - Escudero-Leyva, Efraín; Alfaro-Vargas, Pamela; Muñoz-Arrieta, Rodrigo; Charpentier-Alfaro, Camila; Granados-Montero, María del Milagro; Valverde-Madrigal, Katherine S.; Pérez-Villanueva, Marta; Méndez-Rivera, Michael; Rodríguez-Rodríguez, Carlos E.; Chaverri, Priscila; Mora-Villalobos, J. Aníbal (Frontiers in Agronomy, 2022)
The transition from conventional to organic agriculture is often challenged by the adaptation of biological control agents to environments heavily exposed to agrochemical pollutants. We studied Trichoderma species isolated from living leaf tissues of wild Rubiacaeae (coffee family) plants to determine their fungicide tolerance and potential for bioremoval. First, we assessed the in vitro tolerance to fungicides of four Trichoderma isolates (Trichoderma rifaii T1, T. aff. crassum T2, T. aff. atroviride T3, and T. aff. strigosellum T4) by placing mycelial plugs onto solid media supplemented with seven different systemic and non-systemic fungicides. After a week, most of the fungicides did not significantly inhibit the growth of the isolates, except in the case of cyproconazole, where the only isolate able to grow was T1; however, the colony morphology was affected by the presence of fungicides. Second, biological removal potential was established by HPLC for selected isolates. For this experiment, the isolates T1, T2, and T4 were independently inoculated into liquid media with the fungicides azoxystrobin, chlorothalonil, cyproconazole, and trifloxystrobin. After 14 days of incubation, a removal of up to 89% was achieved for chlorothalonil, 46.4% for cyproconazole, and 33.1% for trifloxystrobin using viable biomass. In the case of azoxystrobin, the highest removal (82.2%) occurred by adsorption to fungal biomass. Ecotoxicological tests in Daphnia magna revealed that T1 has the highest removal potential, achieving significant elimination of every fungicide, while simultaneously detoxifying the aqueous matrix (except in the case of cyproconazole). Isolate T4 also exhibited an intermediate efficiency, while isolate T2 was unable to detoxify the matrix in most cases. The removal and detoxification of cyproconazole failed with all the isolates. These findings suggest that endosphere of wild plants could be an attractive guild to find new Trichoderma species with promising bioremediation capabilities. In addition, the results demonstrate that attention should be placed when combining certain types of agrochemicals with antagonistic fungi in Integrated Pest and Disease Management strategies or when transitioning to organic agriculture.